Study of Structural Properties of Mesoporous Carbon From Fructose with Zinc Borosilicate Activator - Setianingsih, Tutik; Kartini, Indriana; Arryanto, Yateman (The Journal of Pure and Applied Chemistry Research, 2014)
Structural properties, including pore structure, functional group of carbon surface, and crystal structure of carbon built by zinc borosilicate (ZBS) and ZnCl2 (Z) have been investigated in this work. Physically, ZBS and ZnCl2 may act as template of carbon, whereas the Zn(II) cation act as chemical activator of carbonization. All precursors of ZBS (silicagel, boric acid, and ZnCl2) may act as catalysts of caramelization. The caramelization was conducted hydrothermally at 85oC and thermally 130oC. The carbonization was conducted at 450oC. The resulted carbons were washed by using HF 48% solution, 1M HCl solution, and aquadest respectively. The solid products were characterized by using nitrogen gas adsorption, infrared spectrophotometry, X-ray diffraction, and Transmition Electron Microscopy. Result of research showed that ZBS built larger mesopore volume, larger pore domination of pore size, more hydrophobic carbon, and more amorf than ZnCl2.